2006
DOI: 10.1016/j.cub.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Marine Ecology: Gelatinous Bells May Ring Change in Marine Ecosystems

Abstract: Gelatinous plankton are critical components of marine ecosystems. Recent studies are providing evidence of increased population outbursts of such species. Jellyfish seem to respond when an ecosystem is over-fished, and their ecology is under-researched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 11 publications
2
83
0
1
Order By: Relevance
“…So it may be asked, for instance, whether the proliferation of jellyfish off the coast of Namibia and the associated decline in fish stocks there (Lynam et al, 2006) might result from too few turtles or, to put it the other way round, whether increased numbers of leatherbacks would result in a rebound of fish stocks. A number of other problems are associated with massive blooms of jellyfish (Hay, 2006), so it may be wise to attend to what is happening to species higher up on the food chain, such as leatherbacks.…”
Section: Discussionmentioning
confidence: 99%
“…So it may be asked, for instance, whether the proliferation of jellyfish off the coast of Namibia and the associated decline in fish stocks there (Lynam et al, 2006) might result from too few turtles or, to put it the other way round, whether increased numbers of leatherbacks would result in a rebound of fish stocks. A number of other problems are associated with massive blooms of jellyfish (Hay, 2006), so it may be wise to attend to what is happening to species higher up on the food chain, such as leatherbacks.…”
Section: Discussionmentioning
confidence: 99%
“…A number of stressors that include natural ecological fluctuations, anthropogenic activity (e.g., eutrophication; Arai 2001; Richardson et al 2009), overfishing, habitat modification, chemical pollution, and introduction of exotic species in the marine environment (Hay 2006;Purcell 2007;Richardson et al 2009) are suggested causes of these blooms. Climatic changes that alter temperatures, and nutrient fluxes also favor jellyfish; they therefore often strike in ecosystems that are out of balance (Lynam et al 2005;Hay 2006;Purcell 2007;Halpern et al 2008). The most important direct negative consequences of jellyfish blooms are economic losses, which include reduced tourism in affected areas due to stinging danger.…”
Section: Jellyfishmentioning
confidence: 99%
“…The most important direct negative consequences of jellyfish blooms are economic losses, which include reduced tourism in affected areas due to stinging danger. It can also reduce fish catches of artisanal and commercial fishers due to damage to net gear, stinging danger and the resultant longer working hours required to clean and fix fishing nets (Quiñones et al 2013), fish mortality due to stinging, oxygen deprivation in the aquaculture industry, and blocking of water inlets of power plants (Hay et al 1990;Ba mstedt et al 1998;Hay 2006;Purcell 2007). These negative consequences can lead to large economic losses through reduced profits and increasing costs, especially for fisheries (Graham et al 2003;Quiñones et al 2013), as well as to the whole fishing industry at a sector level (Kim et al 2012;Nastav et al 2013).…”
Section: Jellyfishmentioning
confidence: 99%
“…Jellyfish are now recognized as critical indicators and drivers of ecosystem performance and change (Molinero et al 2005;Hay 2006;Lynam et al 2006). Jellyfish mass developments in several coastal areas may allow ecosystem shifts from fish dominance to dominance of gelatinous carnivores, which have been found generally irreversible, as jellyfish may control fish eggs and larvae and compete with fish for food (Lynam et al 2006).…”
Section: Consequences For the Ecosystem Functionmentioning
confidence: 99%